(untitled) (Stamford Journal of Microbiology, 2020)
Spreads are used widely for making the fast foods more amazing and tasty. Varieties and cross combinations of ingredients are used to make many flavours of fast foods. Different restaurants prepare their signature spreads for attracting people but this can cause opposite result if not prepared using high quality raw materials and proper hygienic conditions are not maintained. Current study was conducted on ten different types of spreads (pesto, cilantro, queso, tomato sauce, peanut butter, honey, mustard, cream cheese, chocolate sauce and butter) which are used by the local restaurants in Dhaka city, Bangladesh. Almost all the samples (nine out of ten) harbored total viable bacteria exceeding the standard limit. Four spread samples showed high fungal count (102 cfu/gm). Four samples showed to be positive (˃101/ml recommended acceptable count) for Escherichia coli and Klebsiella spp. which indicates that these spread cannot be recommended for public consumption. Among all the samples examined, only chocolate sauce showed acceptable result without the presence of coliforms, Staphylococcus spp. and Pseudomonas spp. This finding suggests proper maintenance of sanitation in spread preparation and selling area. A proper guidelines and monitoring can help keep up the quality of food additives. Stamford Journal of Microbiology, Vol.10 (1) 2020: 16-19